Strategi Pelatihan dan Pengembangan Sumber Daya Manusia untuk Menghadapi Tantangan Perubahan Organisasi: (Studi di Kantor BPBD Kabupaten Bima) - Syahri Ramadoan; Firman Firman; Sahrul Sahrul (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2023)
The purpose of this research is to explain a strategic approach to the training and development of the Human Resources of the Regional Disaster Management Agency (BPBD) in facing organizational change challenges. This study uses a qualitative descriptive method and a literature study approach. The research is conducted at the Office of the Regional Disaster Management Agency in Bima District. In this research, the data analysis technique used is the interactive model according to Miles and Huberman, which consists of three main components: data reduction, data presentation, and conclusion/verification. The research results show that in the context of natural disasters that are prone in this region, disaster preparedness, disaster management, and emergency response coordination are the top priorities in the training strategy. Involvement of the local community, collaboration with other institutions, and learning from previous experiences are essential elements that can strengthen the readiness of the BPBD in Bima District. Continuous evaluation, career development, utilization of local human resources, and technological innovation are supportive elements in a comprehensive training strategy. Recommendations include the development of long-term training plans, enhanced inter-agency collaboration, and investment in technology that supports disaster management and training. Facing future challenges, such as climate change that can increase the risk of natural disasters, the BPBD in Bima District must continually update their training strategy and ensure that their response to organizational changes and disasters remains relevant and responsive. Therefore, the training and development strategy for HR in the BPBD in Bima District can help strengthen their preparedness and responsiveness in facing the challenges in this region.